Decreasing Phosphatidylcholine on the Surface of the Lipid Droplet Correlates with Altered Protein Binding and Steatosis - Laura Listenberger; Elizabeth Townsend; Cassandra Rickertsen; Anastasia Hains; Elizabeth Brown; Emily G. Inwards; Angela K. Stoeckman; Mitchell P. Matis; Rebecca S. Sampathkumar; Natalia A. Osna; Kusum K. Kharbanda (Cells, 2018)
Alcoholic fatty liver disease (AFLD) is characterized by an abnormal accumulation of lipid droplets (LDs) in the liver. Here, we explore the composition of hepatic LDs in a rat model of AFLD. Five to seven weeks of alcohol consumption led to significant increases in hepatic triglyceride mass, along with increases in LD number and size. Additionally, hepatic LDs from rats with early alcoholic liver injury show a decreased ratio of surface phosphatidylcholine (PC) to phosphatidylethanolamine (PE). This occurred in parallel with an increase in the LD association of perilipin 2, a prominent LD protein. To determine if changes to the LD phospholipid composition contributed to differences in protein association with LDs, we constructed liposomes that modeled the LD PC:PE ratios in AFLD and control rats. Reducing the ratio of PC to PE increased the binding of perilipin 2 to liposomes in an in vitro experiment. Moreover, we decreased the ratio of LD PC:PE in NIH 3T3 and AML12 cells by culturing these cells in choline-deficient media. We again detected increased association of specific LD proteins, including perilipin 2. Taken together, our experiments suggest an important link between LD phospholipids, protein composition, and lipid accumulation.